Comparative Studies of Economic Resilience in Asia-Pacific and European Economies - Valerii Heyets Jhoswa (Journal of Nusantara Economy, 2025)
Economic resilience has become a critical concern in the era of global uncertainty characterized by financial volatility, geopolitical tensions, technological disruption, and post-pandemic recovery dynamics. This study aims to conduct a comparative analysis of economic resilience in Asia-Pacific and European economies by examining how structural factors, governance quality, and policy responses influence their capacity to withstand and recover from economic shocks. The research also seeks to identify key determinants that differentiate resilience patterns across advanced and emerging economies within both regions. A qualitative comparative approach is employed, drawing on secondary data from international organizations such as the World Bank, OECD, IMF, and Asian Development Bank, as well as peer-reviewed scholarly publications and policy reports. The data are analyzed using cross-regional comparative content analysis to identify similarities, divergences, and structural patterns in economic resilience strategies. The findings indicate that European economies demonstrate higher institutional coordination, stronger welfare-based policy mechanisms, and more stable regulatory frameworks, which contribute to sustained recovery capacity. In contrast, Asia-Pacific economies exhibit higher adaptability and growth-oriented resilience driven by industrial diversification, digital transformation, and export-led strategies, although with greater exposure to external shocks and institutional disparities. The study also reveals that digital infrastructure development and governance effectiveness are key mediating variables influencing resilience outcomes in both regions. Theoretically, this research contributes to the literature on comparative political economy by integrating institutional, digital, and policy dimensions of resilience. Practically, it offers policy implications for strengthening adaptive governance, enhancing regional cooperation, and improving crisis-response mechanisms. The study ultimately proposes an integrated resilience framework that bridges regional experiences and provides a foundation for more inclusive and sustainable economic recovery strategies in the global economy.